76-15w=-24

Simple and best practice solution for 76-15w=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 76-15w=-24 equation:


Simplifying
76 + -15w = -24

Solving
76 + -15w = -24

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-76' to each side of the equation.
76 + -76 + -15w = -24 + -76

Combine like terms: 76 + -76 = 0
0 + -15w = -24 + -76
-15w = -24 + -76

Combine like terms: -24 + -76 = -100
-15w = -100

Divide each side by '-15'.
w = 6.666666667

Simplifying
w = 6.666666667

See similar equations:

| f(8)=8+15 | | 5t-3=-2+10 | | 7(7-3)= | | 6x+11=137 | | 4-(3a+2)=14-3a-2 | | -0.7x+1.9y=6.7 | | T=C(3+AB)FORB | | 10x-(5x-8)=48 | | 2/5l-2+3(1-11)=50 | | -10=10(1-9) | | 3x+6x=-9 | | 64x^2-188x-48=0 | | 2.8x-1.6y=3.2 | | T=C(3+AB) | | 8z-7=3z+12 | | 2x+3x-1=5(1-x)+1 | | 2(w^2+3)=w(2w+2) | | 1/4x=-7 | | 57=09v*76 | | 221-53= | | ((3z/2)+z)=((z/3)+13) | | 20n+1=24n-40 | | 4x-8=6x+10 | | -5[25]+2[-3]=x | | x-8.06+7.02=58.604 | | (x+3)(x-7)(3x+5)=0 | | 20n+1=24-40 | | 8x-7y=8 | | 6x-2y=-20 | | 20=2(x+3) | | 6/4+3/4 | | 1=-2-x/2 |

Equations solver categories